Analysis Of The Level Of User Satisfaction Of Tanihub APK Using The Tam Model - Andi Arfian; Adelia Alvi Yana; Hamdum Sulaiman; Astrilyana Astrilyana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study aims to assess the acceptance satisfaction of using the TaniHub Apk for business people and farmers, especially in the agricultural sector. Analysis using the Models Technology Acceptance Model (TAM) is used to describe 5 (five) constructs in this study which include perceived usefulness, perceived ease of use, attitude to war using, behavioral intention to use, & actual usage. This research uses a quantitative approach. Meanwhile, the technique of collecting data is through a survey approach using a purposive sampling technique. The number of respondents is 50 people circulating in 2 districts, namely Bogor and Cianjur districts. The assessment of constructs in this study used a Likert scale. Data analysis used a partial least squares (PLS) approach. The results show that based on 6 (six) hypotheses adopted based on the TAM example that has been tested, hypotheses H1, H4.H6 have a positive & significant effect, while hypotheses H2 and H3 are there is no relationship between Perceived usefulness and Attitude toward usage and Perceived ease of use. affect the attitude toward usage .